Integration of Syrian Refugees and Turkish Students by Non Formal Education Activities - Rüyam Küçüksüleymanoğlu (Institute of Advanced Engineering and Science, 2018)
While 80 percent of Syrian refugee children living in camps have chance to attend formal education, only small number of children are attending Turkish schools. The purpose of this research is to investigate the opinions of the Syrian refugee children before and after non formal education (NFE) activities about refugees’ integration at school. For this purpose, certain activities were created and organized by the researcher. The research was conducted in the selected public school with 73 Syrian children and lasted for 28 weeks. Semi-structured interview and observation methods were used in this study. The data were analysed using content analysis. The findings obtained from the study have been organized into 3 main themes. These themes are “language”, “coping and resolving conflict” and “joining a group and sustaining friendship”. As a result of the study, it has been determined that Syrian children can cope with the problems they are experiencing and integrate into the school life and Turkish students being more helpful and tolerant towards the refugees are influenced by non formal education activities conducted in school. It is hoped that it will be a good example for each school in designing educational programs for Syrian refugee children with NFE activities.